A Proteomics Analysis to Evaluate Cytotoxicity in NRK-52E Cells Caused by Unmodified Nano-Fe3O4 - Yi-Reng Lin; Chao-Jen Kuo; Hugo You-Hsien Lin; Chin-Jen Wu; Shih-Shin Liang (The Scientific World Journal)
We synthesized unmodified Fe3O4 nanoparticles (NPs) with particles size from 10 nm to 100 nm. We cultured NRK-52E cell lines (rat, kidney) and treated with Fe3O4 NPs to investigate and evaluate the cytotoxicity of NPs for NRK-52E cells. Through global proteomics analysis using dimethyl labeling techniques and liquid phase chromatography coupled with a tandem mass spectrometer (LC-MS/MS), we characterized 435 proteins including the programmed cell death related proteins, ras-related proteins, glutathione related proteins, and the chaperone proteins such as heat shock proteins, serpin H1, protein disulfide-isomerase A4, endoplasmin, and endoplasmic reticulum resident proteins. From the statistical data of identified proteins, we believed that NPs treatment causes cell death and promotes expression of ras-related proteins. In order to avoid apoptosis, NRK-52E cell lines induce a series of protective effects such as glutathione related proteins to reduce reactive oxygen species (ROS), and chaperone proteins to recycle damaged proteins. We suggested that, in the indigenous cellular environment, Fe3O4 NPs treatment induced an antagonistic effect for cell lines to go to which avoids apoptosis.